Smart baby trolley / Mohamad Mustaqim Abdullah Sani, Nur Hidayatul Nadihah Abd Wahab and Mohamad Syahmi Zullkiffle - Abdullah Sani, Mohamad Mustaqim; Abd Wahab, Nur Hidayatul Nadihah; Zullkiffle, Mohamad Syahmi (2011)
The “SMART BABY TROLLEY” which consists of one simple sensor which can detects lights. This circuit is designed mainly for the babies’ trolley. This innovation is upgrade due to its functionality, safety and comfortability that will make our life more easily especially to families that have a baby. In this project, we use two combinations of circuit which is control circuit and main circuit. Control circuit consist of LDR that is detect light and variable resistor for adjust the intensity of detected light. In main circuit there are only delays that functions as switch. The operation of the system is when sunny day situation, the roof of the baby trolley automatically will move forward to close it. The motor will function when the LDR detect light. We includes fan cooler as a accessory that operate manually. So, the baby can feel comfortable without any trouble. Besides that, the parent does not worry about the situation their babies. In addition, prospect of smart baby trolley not specific for comfortable aspect only but we also consider the safety respectively. Based on our structure, the material and circuit design we will be using is not hazardous to babies.